Successful Treatment with Rectal tube Placement and Barium Enema in Uncomplicated Acute Sigmoid Volvulus: A Case Report - Stevanus Immanuel Silahooij; Budi Widodo (Indian Journal of Forensic Medicine & Toxicology, 2022)
Sigmoid volvulus is a condition in which sigmoid colon wraps around itself and its own mesentery, which then causes a closed-loop obstruction. This condition accounts for 50-90% cases of twisted large intestine and often affects adults and are commonly found in males. The classic triad signs and symptoms are abdominal pain, distention, and constipation. Although the emergency resection seems to be the right procedure in treating acute sigmoid volvulus, there is still non-surgical treatment often done in several conditions. We reported a 52-years-old male with uncomplicated acute sigmoid volvulus who underwent non-surgical treatment due to his refusal of surgical therapy. Non-surgical treatment was successfully done and no recurrence found within one year. The aim of this report was to emphasize that non-surgical therapy only could be successfully done without surgical treatment.